An improved method of studying user-system interaction by combining transaction log analysis and protocol analysis - Jillian R. Griffiths; R.J. Hartley; Jonathan P. Willson (Information Research: An International Electronic Journal)
The paper reports a novel approach to studying user-system interaction that captures a complete record of the searcher's actions, the system responses and synchronised talk-aloud comments from the searcher. The data is recorded unobtrusively and is available for later analysis. The approach is set in context by a discussion of transaction logging and protocol analysis and examples of the search logging in operation are presented